Perkembangan Moral Remaja - Zahara Lutfya; Imah Yulianti; Linda Yarni (Universitas 45 Surabaya, 2024)
Adolescent moral development is an important process in the formation of individual character and personality. This research aims to understand various factors that influence moral development in adolescents, including the influence of the family environment, education, and social interactions. Apart from that, this research also explores the role of technology and social media in shaping the moral values ​​of teenagers in the digital era. The research methods used include surveys, in-depth interviews and participant observation. The research results show that family support, the quality of moral education in schools, and a positive social environment contribute significantly to good moral development in adolescents. However, it was also found that exposure to negative content on social media can hinder moral development. This research suggests the need for collaboration between families, schools and communities in creating an environment that supports the healthy and positive moral development of adolescents.